2015
DOI: 10.1167/iovs.14-15633
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Foveal Thickness and Architecture After Macula-Off Retinal Detachment Repair

Abstract: Optical coherence tomography scans taken serially at the same location showed a progressive increase of HNL+ONL, ELM-EZ, and EZ-RPE thicknesses and restoration of the integrity of outer retinal bands after repair of fovea-off RRD. The use of software able to rescan at exactly the same area is crucial to correctly follow and interpret the reconstitution of the retinal bands and to correlate them to BCVA recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
78
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 26 publications
6
78
2
1
Order By: Relevance
“…Two recent studies reported the thickness of retinal layers was significantly thinned after successful attachment and gradually increased, with only EZ-RPE thickness remaining thinner than the opposite, unaffected eye at 12 months postoperatively. 28,29 Our results corroborate those findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Two recent studies reported the thickness of retinal layers was significantly thinned after successful attachment and gradually increased, with only EZ-RPE thickness remaining thinner than the opposite, unaffected eye at 12 months postoperatively. 28,29 Our results corroborate those findings.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies 28,29 evaluated the relationship between improvements in BCVA and thickness of EZ-RPE or ELM-EZ at particular time points postoperatively FIGURE 3. Changes in mean retinal layer thickness are shown in eyes with macula-off RRD after surgery and corresponding control eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual acuity in the gas group was not statistically different from the visual function in the SiO group. Recent SD-OCT studies in macula-off RRD revealed that the postoperative visual acuity correlates with thickness and especially structural integrity of the outer retinal layers (e.g., external limiting membrane, ellipsoid zone, cone interdigitation zone) [27,28] . These morphological parameters may interfere with a possible deterioration of the visual function due to retinal thinning of the inner layers and makes evaluation of reported visual loss after SiO tamponade difficult [16][17][18][19][20][21][22][23][24]29] .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies quantitatively analyzed photoreceptor restoration over time after repair of RD. 15,16 Investigators have also described the dependence of photoreceptor recovery on the integrity of the external limiting membrane (ELM) after RD repair, [17][18][19] whereas others have shown that IS/OS layer restoration is independent of ELM integrity. 12,20 We performed a retrospective, quantitative SD-OCT study to examine the course of photoreceptor volumetric changes in patients with macula-off RDs after successful repair.…”
mentioning
confidence: 99%